2021
DOI: 10.1182/bloodadvances.2020003944
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic interactions in the microenvironment in vivo activate an antiapoptotic multidrug-resistant phenotype in CLL

Abstract: The Bcl-2 inhibitor venetoclax (VEN) has yielded exceptional clinical responses in chronic lymphocytic leukemia (CLL). However, de novo resistance can result in failure to achieve negative minimal residual disease and predicts poor treatment outcomes. Consequently, additional pro-apoptotic drugs, such as inhibitors of Mcl-1 and Bcl-xL, are in development. By profiling anti-apoptotic proteins using flow cytometry, we find that leukemic B-cells recently emigrated from the lymph node (LN) (CD69Pos/CXCR4Low) in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 88 publications
(168 reference statements)
6
26
0
Order By: Relevance
“…Of relevance, tumor microenvironment may determine an additional support in maintaining the expression of Notch2 and Mcl-1, especially at the lymph node level. This is in line with emerging clinical data that suggest an involvement of lymph node niches to induce resistance to proapoptotic treatments ( 38 ).…”
Section: Discussionsupporting
confidence: 87%
“…Of relevance, tumor microenvironment may determine an additional support in maintaining the expression of Notch2 and Mcl-1, especially at the lymph node level. This is in line with emerging clinical data that suggest an involvement of lymph node niches to induce resistance to proapoptotic treatments ( 38 ).…”
Section: Discussionsupporting
confidence: 87%
“…Mcl-1 was recognized among the top molecule in cancers for somatic copy number alterations (34). Mcl-1 protein levels have been shown to be important in the survival of CLL cells (20,21,(35)(36)(37)(38)(39)(40)(41). Recently, direct inhibitors of Mcl-1 have been designed by Astra Zeneca [AZD-5991 (42)], Amgen [AMG-176 (43,44)] and Novartis [S63845 and S64315 (45,46)].…”
Section: Introductionmentioning
confidence: 99%
“…While the first one is enriched in recently born/divided cells mostly present in lymphoid tissues that can be also found in peripheral blood as a small proportion of recently emigrant CLL cells, the “quiescent fraction” enriched in older, less vital cells, are mostly present in peripheral blood and need to immigrate to lymphoid tissue or die ( 42 ). Two independent groups recently demonstrated that in treatment naïve patients the small proportion of recently emigrant CLL cells overexpress anti-apoptotic proteins including MCL-1 and BCL-XL ( 9 , 10 ). Of note, this subpopulation survives and increases upon in vivo venetoclax treatment of the patients showing that resistant CLL cells already exist, even in untreated CLL patients and these cells persist during proapoptotic treatment with venetoclax ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple independent mechanisms contributed to venetoclax resistance, including the acquisition of various mutations in BCL-2 and/or the upregulation of other anti-apoptotic proteins which are not targeted by venetoclax, such as BCL-XL and MCL-1 ( 7 , 8 ). Different groups reported that malignant cells that recently interacted in vivo with the supportive microenvironment of lymphoid tissues ( 9 , 10 ), or those that were cultured in vitro with different signals that mimic microenvironment stimuli ( 11 15 ), show an increased expression of BCL-XL and MCL-1 and are less sensitive to venetoclax compared to quiescent or unstimulated CLL cells. In line with this, we previously reported that when peripheral blood mononuclear cells (PBMC) from CLL patients were incubated on immobilized anti-CD3 monoclonal antibodies (aCD3) to induce T cell activation, autologous activated T lymphocytes induced the activation of CLL cells, and in vitro venetoclax resistance due to the upregulation of BCL-XL and MCL-1 ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%